Multifunctional MoS2 Transistors with Electrolyte Gel Gating. Issue 22 (30th April 2020) - Wu, Binmin; Wang, Xudong; Tang, Hongwei; Jiang, Wei; Chen, Yan; Wang, Zhen; Cui, Zhuangzhuang; Lin, Tie; Shen, Hong; Hu, Weida; Meng, Xiangjian; Bao, Wenzhong; et al.
Abstract: MoS2, one of the most valued 2D materials beyond graphene, shows potential for future applications in postsilicon digital electronics and optoelectronics. However, achieving hole transport in MoS2, which is dominated by electron transport, is always a challenge. Here, MoS2 transistors gated by electrolyte gel exhibit the characteristics of hole and electron transport, a high on/off ratio over 10 5, and a low subthreshold swing below 50 mV per decade. Due to the electrolyte gel, the density of electrons and holes in the MoS2 channel reaches ≈9 × 10 13 and 8.85 × 10 13 cm −2, respectively. The electrolyte gel‐assisted MoS2 phototransistor exhibits adjustable positive and negative photoconductive effects. Additionally, the MoS2 p–n homojunction diode affected by electrolyte gel shows high performance and a rectification ratio over 10 7 . These results demonstrate that modifying the conductance of MoS2 through electrolyte gel has great potential in highly integrated electronics and optoelectronic photodetectors. Abstract : This work demonstrates MoS2 field effect transistors (FETs) with electrolyte gel gating, achieving flexible modulation of carrier concentration and type in MoS2 . The MoS2 FETs exhibit high‐performance negative photoconductive detection, because the deposited Au nanoparticles on the surface of MoS2 act as traps. Additionally, a MoS2 homogeneous p–n junction diode with a high rectification ratio is realized.